HUBUNGAN TINGKAT KEPUASAN PASIEN MISKIN PENGGUNA BPJS TERHADAP KINERJA PELAYANAN KESEHATAN DI RSUD ULIN BANJARMASIN TAHUN 2016 - Fakhsiannor Fakhsiannor (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The hospital is as a health service that functions primarily organizes health effort that is healing and recovery of patients, which provides services to the public regardless of social kulturnya. In support of the implementation of public health assurance program (BPJS) hospital has a very important role in providing services to the poor. In preliminary studies to 20 respondents, there were 12 respondents (60%) declare non puasan and 8 respondents (40%) expressed their satisfaction with the performance of medical services at the hospital Ulin Banjarmasin. This research aims to find out the level of patient satisfaction Guarantee public health with the performance of the health service in general hospital Ulin Banjarmasin in Central Kalimantan, covering the five dimensions of service i.e. reliability, responsiveness, assurance, empathy and physical evidence. This type of research Survey with Analytic design Crossectional. Population studies are all patient health care Community who visited the Hospital General Ulin Banjarmasin in during the period of research, whereas samples taken by Accidental Sampling, as many as 93 respondents. The collection of data through interviews using questionnaire. The results showed that of the 5 variables examined is reliability, responsiveness, empathy and reassurance, physical evidence against the performance of health service officers at the Hospital found 5 related variables are meaningful.